Real and Financial Sector Linkages in China and India - Aziz, Jahangir (IMF Working Papers; Working Paper, 2008)
In the spirit of what is known as business cycle accounting, this paper finds that the investment wedge-the gap between household's rate of intertemporal substitution and the marginal product of capital-is large and quantitatively significant in explaining China's and India's growth. Specific financial sector policies are shown to map well the size and changes in the investment wedge. In the case of China, nonperforming loans, borrowing constraints, and uncertainty over changes in government guidance in bank lending, have implied large transfers from households to firms that have kept capital cost low and encouraged investment. In the case of India, post-1992 financial sector reforms, particularly the reduction in the funds preempted by the government from the banking system, has played an important role in reducing the cost of capital. Simulations show that for rebalancing growth in China and sustaining high investment rate in India, further financial sector reforms could turn out to be key.